Analisis Fundamental Price Earning Ratio Dengan Variabel Intervening Price To Book Value: Analysis Fundamental On Price Earning Ratio with Intervening Variable Price To Book Value - Aprila Dwi Rahmawati; Rifda Nabila (Jurnal Ilmiah Produktif, 2022)
This research aims to examine the effect of the current ratio, return on equity and debt to equity ratio on the price earning ratio with price to book value as an intervening variable. In analyzing stocks that will later be used as investment options, it must be done correctly. One approach commonly used by investors is the Price Earning Ratio (PER) method, because PER is a measure of a company's performance that can result in an increase or decrease in the market price of a company's stock. The data used in this study is the financial statements of Islamic banks in the second quarter of 2018 until the fourth quarter of 2021. This research is a type of quantitative research with an analytical tool in the form of Path Analysis. The population of this study is Islamic banks listed on the Indonesia Stock Exchange with purposive sampling technique. The results showed that DER and PBV had a positive effect on PER, while CR and ROE had a negative effect on PER. In addition, CR and DER have no effect on PBV, and ROE has a positive effect on PBV. In this study, PBV can be a mediating variable for ROE to PER but cannot mediate CR and DER to PER. Keywords: Sharia Banking,current ratio, return on equity, debt to equity ratio, price earning ratio, price to book value